Expression of miR-33 from an SREBP2 intron inhibits the expression of the fatty acid oxidation-regulatory genes CROT and HADHB in chicken liver. Issue 2 (4th March 2019) - Shao, F.; Wang, X.; Yu, J.; Shen, K.; Qi, C.; Gu, Z.
ABSTRACT: 1. Limiting the growth of adipose tissue in chickens is a major issue in the poultry industry. In chickens, de novo synthesis of lipids occurs primarily in the liver. Thus, it is necessary to understand how fatty acid accumulation in the liver is controlled. The miR-33 is an intronic microRNA (miRNA) of the chicken sterol regulatory element binding transcription factor 2 ( SREBF2 ), which is a master switch in activating many genes involved in the uptake and synthesis of cholesterol, triglycerides, fatty acids and phospholipids. 2. In the current study, the genes CROT and HADHB known to encode enzymes critical for fatty acid oxidation were predicted to be potential targets of miR-33 in chickens via the miRNA target prediction programs 'miRanda' and 'TargetScan'. Co-transfection and dual-luciferase reporter assays showed that the expression of luciferase reporter gene linked to the 3ʹ-untranslated region (3ʹUTR) of the chicken CROT and HADHB mRNA was down-regulated by overexpression of the chicken miR-33 ( P < 0.05). This down-regulation was completely abolished when the predicted miR-33 target sites in the CROT and HADHB 3ʹUTR were mutated. 3. Transfecting miR-33 mimics into the LMH cells led to a decrease in the mRNA expression of CROT and HADHB ( P < 0.01), and this transfection had a similar effect on the proteins ( P < 0.05). In contrast, the expression of CROT in primary chicken hepatocytes was up-regulated after transfection with the miR-33 inhibitor LNA-anti-miR-33 ( P < 0.05). 4. Using quantitative RT-PCR, it was shown that the expression of miR-33 was increased in the chicken liver from day 0 to day 49 of age, whereas the CROT and HADHB mRNA levels decreased during the same period. 5. These findings support the conclusion that miR-33 might play an important role in lipid metabolism in the chicken liver by negatively regulating the expression of the CROT and HADHB genes, which encode enzymes critical for lipid oxidation.